(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: The proinflammatory protein TNF-alpha (TNF- α) is one of the pathophysiologies that has been thought to be influenced by inflammatory cytokines. As tissue damage agents and a biomarker for periodontal disease development, TNF-α levels are higher in the oral fluids of smokers. Recent developments have made it possible to utilize saliva as a diagnostic fluid to identify the concentrations of these biomarkers. Methods: Before and after phase-I therapy, salivary TNF- levels were measured in nonsmokers with chronic periodontitis (control group, n=15) and in smokers with chronic periodontitis (study group, n=15). The results were compared with clinical parameters like gingival bleeding index, plaque index, probing pocket depth, and clinical attachment level. Results: At baseline, smokers had higher salivary TNF- α than nonsmokers. Both smokers and nonsmokers saw a clinical parameter and salivary TNF-α level decrease that was statistically significant (p=0.00) three months following Phase-I treatment. However, compared to smokers, nonsmokers had a substantially higher decrease in clinical parameters and salivary TNF-α levels. Conclusion: The current data demonstrate that smoking is related to increased levels of salivary TNF-α and that nonsmokers respond better to phase-I treatment than smokers, as seen by a considerable drop in salivary TNF-α levels.